Mineral nanoparticles and nanocomposite hydrogels with osteoinductive properties for bone regeneration - Cho-E Choi; Arghya Paul (Exploration of BioMat-X)
Mineral nanoparticles and osteoinductive biomaterials are essential in advancing bone regeneration by addressing skeletal conditions and injuries that compromise structural integrity and functionality. These biomaterials stimulate the differentiation of precursor cells into osteoblasts, creating biocompatible environments conducive to bone tissue regeneration. Among the most promising innovations, mineral-based nanoparticles and nanocomposite hydrogels have emerged as effective strategies for enhancing osteoinductive potential. This review explores the diverse types of osteoinductive biomaterials, including natural sources, synthetic compounds, and hybrid designs that incorporate mineralized nanoparticles. Emphasis is placed on polymeric hydrogels as delivery platforms for these materials, highlighting their dual role as structural supports and bioactive agents that promote osteogenesis. Challenges such as immune rejection, biodegradability, mechanical stability, and short in vivo residence time are critically discussed, alongside their impact on clinical translation. By presenting a comprehensive analysis of mechanisms, applications, and limitations, this review identifies opportunities for integrating osteoinductive biomaterials with emerging fields like immunology and biomechanics. Ultimately, this work aims to provide actionable insights and advance the development of novel, clinically relevant solutions that improve patient outcomes and address the growing global need for effective bone repair and regeneration.